2017
DOI: 10.1007/s40291-017-0259-y
|View full text |Cite
|
Sign up to set email alerts
|

Epi proColon® 2.0 CE: A Blood-Based Screening Test for Colorectal Cancer

Abstract: Epi proColon 2.0 CE is a blood-based test designed to aid in the early detection of colorectal cancer. The test comprises a qualitative assay for the polymerase chain reaction (PCR) detection of methylated Septin9 DNA, the presence of which is associated with colorectal cancer: however, positive results should be verified by colonoscopy or sigmoidoscopy. Epi proColon 2.0 CE discriminated between patients with colorectal cancer and healthy controls with high clinical sensitivity and specificity in pivotal case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
122
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 22 publications
4
122
1
2
Order By: Relevance
“…17 Epi proColon 2.0 assay, a blood ctDNA-based SEPT9 methylation assay for CRC screening, has recently been approved by both FDA and Chinese FDA. 26 It showed a sensitivity of 68.2% and a specificity of 78.2% in a large cohort study with 1/3 algorithm. 27 Another clinical trial reported that its sensitivity for detecting stage I CRC was as low as 35.0%.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…17 Epi proColon 2.0 assay, a blood ctDNA-based SEPT9 methylation assay for CRC screening, has recently been approved by both FDA and Chinese FDA. 26 It showed a sensitivity of 68.2% and a specificity of 78.2% in a large cohort study with 1/3 algorithm. 27 Another clinical trial reported that its sensitivity for detecting stage I CRC was as low as 35.0%.…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, DNA methylation testing in bodily fluids represents a powerful diagnostic tool in the clinical management of malignant diseases . Epi proColon 2.0 assay, a blood ctDNA‐based SEPT9 methylation assay for CRC screening, has recently been approved by both FDA and Chinese FDA . It showed a sensitivity of 68.2% and a specificity of 78.2% in a large cohort study with 1/3 algorithm .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epi proColon 2.0 CE: Technical aspects and clinical performance for version 2.0 of the test were recently summarized [31]. The optimized assay was first CE certified as Epi proColon 2.0 for the European and world market excluding the US.…”
Section: Epi Procolon 20 and The Us Fda Pma Approved Epi Procolonmentioning
confidence: 99%
“…Test performance (Table 1) was evaluated in a number of case control studies in Europe and China [27,[31][32][33][34]. As outlined in these studies, test sensitivity was reported to range from 73-81% and test specificity was reported to range from 96-99%.…”
Section: Epi Procolon 20 and The Us Fda Pma Approved Epi Procolonmentioning
confidence: 99%